Pengaruh Kapasitas Absorptif dan Situs Jejaring Sosial Terhadap Kinerja Inovasi Usaha Mikro Kecil dan Menengah (UMKM) di Indonesia - Prita Ayu Kusumawardhany (Universitas Airlangga, 2018)
Global competition in the digital era is currently encouraging Micro, Small and Medium Enterprises (SMEs) in Indonesia to develop innovations to provide competitive advantage. SMEs must be able to be adaptive to be able to absorb knowledge, especially in the field of technology. The use of social networking sites can provide a lot of information about individuals and networks that can be used for business purposes. The purpose of this study was to show the relevance of absorptive capacity and the role of social networking sites towards innovations conducted by SMEs. This research is a quantitative by using survey method processed through Partial Least Square (PLS) - Path Modeling that measures absorptive capacity relationships, social networking sites with innovation performance. One hundred (100) questionnaires have been distributed to SMEs in Indonesia. Research results show that the increased absorptive capacity of SMEs through social networking sites can improve innovation performance. Therefore, several recommendations are needed so those SMEs in Indonesia know what must be done to strengthen innovation performance.